Eigenvalues and ranges for perturbations of nonlinear accretive and monotone operators in Banach spaces - Zhou Haiyun; Athanassios G. Kartsatos (Abstract and Applied Analysis)
Various eigenvalue and range results are given for perturbations of m-accretive and maximal monotone operators. The eigenvalue results improve and extend some recent results by Guan and Kartsatos, while the range theorem gives an affirmative answer to a recent problem of Kartsatos.